DO FINANCIAL RATIO PREDICTING FINANCIAL DISTRESS IN LOCAL GOVERNMENT - Melati Tegari Islamiyah; Ifa Ratifah; Firdaus Firdaus (Faculty of Economic and Business, University of Pasundan, 2022)
This study was conducted with the aim of testing and analyzing the effect of financial independence and the degree of decentralization on financial distress in districts and cities in West Java province for the 2015-2019 period. The sampling technique used is non-probability sampling with sampling the sample is saturated sampling. The method used in this research is descriptive and verification method. The data collection technique used was secondary data obtained from the Supreme Audit Agency (BPK). The population of this study is all districts and cities in West Java Province in the 2015-2019 Fiscal Year. The number of regencies and cities in West Java Province in the 2015-2019 Fiscal Year is 27. The results of data analysis show that financial independence has a negative effect on financial distress and the degree of decentralization has a positive effect on financial distress